PERANCANGAN SISTEM INFORMASI TABUNGAN SISWA MENGGUNAKAN METODE RAD (RAPID APPLICATION DEVELOPMENT )BERBASIS WEB - Dwipa Handayani; Hendarman Lubis (JURNAL REKAYASA INFORMASI, 2022)
Savings is one of the various kinds of banking products that are most in demand by the public, ranging from students, entrepreneurs, and the general public. Data collection methods used in this study, namely observation, interviews, literature study, literature study, questionnaires, and system development methods. The system development method used in the development of learning media applications to train the motoric skills of children with special needs based on Android is the RAD (Rapid Application Development) method. System functional testing is done using black box testing. With the development of a student savings information system, it is easier for teachers to process student savings transactions and withdrawals of student savings so as to reduce the risk of damage or loss. Keywords: Rapid Application Development, Information Systems, Students, Savings, web